RETRACTED: Linkages Between Knowledge Management Process and Corporate Sustainable Performance of Chinese Small and Medium Enterprises: Mediating Role of Frugal Innovation - Kun, Ma (Frontiers in Psychology, 2022)
In the contemporary world, frugal innovation is the most discussed area to enhance corporate sustainable performance in manufacturing firms. The knowledge management process is also a key determinant of frugal innovation. Existing literature is limited to knowledge management and its impact on corporate sustainable performance. This study aims to determine the effect of the knowledge management process (acquisition, dissemination, application) on sustainable corporate performance with the association of frugal innovation. The survey method was used to collect data from 356 SMEs in China. Structure equation modelling was applied to obtain the results of collected data. Results show that all three dimensions of knowledge management have a significant impact on corporate sustainable performance. Furthermore, frugal innovation also has a significant and positive impact on corporate sustainable performance. Results further show that frugal innovation partially mediates the relationship of the knowledge dissemination, knowledge application and sustainable corporate performance but no mediation role frugal innovation was found between knowledge acquisition and corporate sustainable performance. The findings of this study will provide useful insights for experts and manufacturers. It will help to understand the role of KM in their organizational behaviour by being an economical manufacturing process. This study underscored the importance of the KMP to policymakers. In countries such as China that have global orders, KM is an essential determinant of FI. KM is a tool used to achieve CSP goals inside and outside of an enterprise, thus the development firms need to focus on KM.